Round Window Application of an Active Middle Ear Implant: A Comparison With Hearing Aid Usage in Japan. Issue 6 (July 2017) - Iwasaki, Satoshi; Usami, Shin-ichi; Takahashi, Haruo; Kanda, Yukihiko; Tono, Tetsuya; Doi, Katsumi; Kumakawa, Kozo; Gyo, Kiyofumi; Naito, Yasushi; Kanzaki, Sho; Yamanaka, Noboru; Kaga, Kimitaka
Abstract : Objective: To report on the safety and efficacy of an investigational active middle ear implant (AMEI) in Japan, and to compare results to preoperative results with a hearing aid. Design: Prospective study conducted in Japan in which 23 Japanese-speaking adults suffering from conductive or mixed hearing loss received a VIBRANT SOUNDBRIDGE with implantation at the round window. Postoperative thresholds, speech perception results (word recognition scores, speech reception thresholds, signal-to-noise ratio [SNR]), and quality of life questionnaires at 20 weeks were compared with preoperative results with all patients receiving the same, best available hearing aid (HA). Results: Statistically significant improvements in postoperative AMEI-aided thresholds (1, 2, 4, and 8 kHz) and on the speech reception thresholds and word recognition scores tests, compared with preoperative HA-aided results, were observed. On the SNR, the subjects' mean values showed statistically significant improvement, with −5.7 dB SNR for the AMEI-aided mean and −2.1 dB SNR for the preoperative HA-assisted mean. The APHAB quality of life questionnaire also showed statistically significant improvement with the AMEI. Conclusion: Results with the AMEI applied to the round window exceeded those of the best available hearing aid in speech perception as well as quality of life questionnaires. There were minimal adverse events or changes to patients' residual hearing.